FACTORS ASSOCIATED WITH HISTORY OF EXCLUSIVE BREASTFEEDING AT MAHDARINA PRATAMA CLINIC MEDAN SELAYANG DISTRICT OF MEDAN CITY: Riwayat pemberian ASI Eksklusif - Safitri, Mey Elisa; Us, Hafsah (Poltekkes Kemenkes Medan, 2024)
Breastfeeding is a special pride for a woman to her baby. According to data from the WHO in 2017 globally, less than 40% of infants fewer than 6 are exclusively breastfed and the rest have been given complementary foods. The impact that will occur for the mother is the risk of breast cancer, ovarian cancer, uterine cancer, porous bones, maternal diabetes, stress, and anxiety. While the impact on infants is gastrointestinal infections, respiratory infections, risk of allergies, risk of decreased intelligence, risk of obesity, risk of vascular disease, risk of diabetes, risk of cancer in children, risk of chronic disease. This study aimed to analyze factors associated with history of exclusive breastfeeding at Mahdarina Pratama Clinic, Medan Selayang District, Medan City. This was analytical survey research with a cross sectional design. The population was mothers who had babies aged 7-12 months who came to the Clinic totaling 53 people and all of them were used as research samples. The data used primary data and tested by Chi Square test.The results of this study indicated that the majority of knowledge factors were knowledgeable enough was 41.5%, negative attitudes was 54.7%, the majority of mothers work 50.9%. The results of the Chi-Square test found knowledge p = 0.024 <0.05, attitude p = 0.035 <0.05 and work p = 0.002 <0.05.The conclusion shows that there is a relationship between knowledge, attitudes and work with a history of exclusive breastfeeding at Mahdarina Pratama Clinic, Medan Selayang District, Medan City. It is ecpevted to nursing mothers to pay more attention to information about exclusive breastfeeding through print and social media, especially working mothers. Keywords: knowledge; attitude; occupation; history of exclusive breastfeeding